2020
DOI: 10.1186/s13104-020-05252-6
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between nonculprit stenosis follow-up iFR and FFR after STEMI (iSTEMI substudy)

Abstract: Objective: To evaluate agreement between instantaneous wave free ratio (iFR) and fractional flow reserve (FFR) for the functional assessment of nonculprit coronary stenoses at staged follow-up after ST-segment elevation myocardial infarction (STEMI). Results: We measured iFR and FFR at staged follow-up in 112 STEMI patients with 146 nonculprit stenoses. Median interval between STEMI and follow-up was 16 (interquartile range 5-32) days. Agreement between iFR and FFR was 77% < 5 days after STEMI and 86% after ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In another iSTEMI substudy, the same authors concluded that the time interval between STEMI and the physiologic interrogation impact the agreement between FFR and iFR: the longer delay, the better the agreement. 32 A recent review concluded that transient changes in physiology immediately after STEMI may result in iFR overestimating and FFR underestimating nIRA lesion significance. 33 On the other hand, in a porcine model of microvascular injury, FFR was shown to be unchanged in remote (“nonculprit”) vessels 34 ; of note, 97% of the nIRA with discrepant FFR and Pd/Pa were remote from the IRA in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In another iSTEMI substudy, the same authors concluded that the time interval between STEMI and the physiologic interrogation impact the agreement between FFR and iFR: the longer delay, the better the agreement. 32 A recent review concluded that transient changes in physiology immediately after STEMI may result in iFR overestimating and FFR underestimating nIRA lesion significance. 33 On the other hand, in a porcine model of microvascular injury, FFR was shown to be unchanged in remote (“nonculprit”) vessels 34 ; of note, 97% of the nIRA with discrepant FFR and Pd/Pa were remote from the IRA in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 74 Currently, it is unknown how long these effects remain present after myocardial infarction. 75 …”
Section: Practical Aspects and Patient Selectionmentioning
confidence: 99%
“…The physiological changes during STEMI may impact the classi cation disagreement in the more extended follow-up period [21]. It was noted that iFR could overdiagnose the severity of stenoses, and FFR can undervalue in the acute and subacute phases in STEMI patients [22]. Theoretically, the iFR could be used in ACS patients [23], but it still prolongs procedure time, requires pressure wire and makes the procedure costly.…”
Section: Introductionmentioning
confidence: 99%